Choosing a Method of Explaining Unfamiliar Words in Elementary School Textbooks Depending on Their Nature (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article analyzes the scientific and theoretical basis of using dictionaries in primary education.